SUDDEN CARDIAC DEATH IN FORENSIC MEDICAL PRACTICE: THE ROLE OF HEART DISEASES - Razikova Dilnoza Kadirovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Summary. Sudden cardiac death is a condition that turns into unconscious death and manifests itself within 1 hour with acute symptoms and is accompanied by cardiac pathology. The fact that diseases of the circulatory system are associated with dysfunction of the cardiovascular system in the aggregate is one of the pathologies proven by clinical and pathological studies. Recently, the pathology of coronary heart disease has attracted the attention of our medical staff with frequent cases of "sudden cardiac death" and has caused many controversial situations. For this, a histopathological examination of the tissue of the cardiac myocardium is carried out using materials obtained during the autopsy of the corpses of patients who died from various diseases. The aim of the study is to supplement data on cardiac pathologies.